Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1996)
Table of Content Back to the Future: Charles Long & Sterolab by Mark van der Walle Gary Hume Definitely Something by Lionel Bovier Lacquer Syringe by Gregor Muir Skin Jobs by Douglas Fogle Gabriel Orozco Back in Five Minutes by Francesco Bonami The Os of Orozco by M. Catherine de Zegher Pipilotti Rist The Mechanis of Fluids by Nancy Spector Pipilotti Rist’s Flying Room by Philip Ursprung The Rist Risk Factor by Marius Babis Shooting Divas by Marius Babias Conversation in the Lobby of a Hotel in Berlin by Laurie Anderson and Pipilotti Rist Rudy Burckhardt, Insert Up Above My Head – Bruce Connor by Faye Hirsch Rudy Burckhardt, A Short Biographical Sketch by Vincent Katz Pillow Talk in Public Space, Cumulus from Europe by Nadia Schneider & Angela Bullock All of These and None of These, The 1996 New York Video Festival, Cumulus from America by Graham Leggat From Art to Lifestyle . . . and Back Again by Christoph Doswald.
In this issue of Parkett, certain artistic canons have gently loosed their moorings. From Nancy Spector’s observations on Pipilotti Rist’s art, one might be led to discover an aesthetics of fluidity. Our cover is also in gentle flux with a luminous parachute-flower, an ephemeral, sculptural hybrid. Gabriel Orozco staged and captured this phenomenon, demonstrating one of his favorite motifs: his fascination with dissection and transformation. The segmented white shape is both flower and parachute, picture and sculpture, image and event, but it is also a piece of silk with visible cuts and seams blowing in the wind —quintessential symbol of transience. Video artist Pipilotti Rist has put herself in purgatory and begs her audience for help through a crack in the floor. This piece, titled SELFLESS IN THE LAVA BATH, hotly undermines the idea of electronic media as a cold stream of images. Similarly, for a fugitive moment, her FLYING ROOM, suspended in the lobby of a bank, transforms the television set into the harbinger of a social utopia. Waiting customers whose gaze wanders will discover a selection of topsy-turvy furnish¬ings that seem to be floating off to nowhere high above their heads. And to top it off, the people cavorting overhead as stars of Rist’s video clips are down below on the ground as well, serving clients. It so happens that all three collaboration artists were born in 1962 —in Kent (England), Jalapa (Mexico), and Grabs (Switzerland). Could that have anything to do with the fact that they share a certain preoccupation with things that flow? The Insert is b Rudy Burckhardt. (editorial by publisher)
boek
Keywords: Hume, Gary; Rist, Pipilotti; Orozco, Gabriel